Comparison of the effects of rapid maxillary expansion and alternate rapid maxillary expansion and constriction protocols followed by facemask therapy - ÖNEM ÖZBİLEN, ELVAN; YILMAZ, HANİFE NURAY (KOREAN ASSOC ORTHODONTISTS, 2019)
Objective: The aim of this retrospective study was to evaluate and compare the changes in the pharyngeal airway (PA), maxillary sinus volume, and skeletal parameters after rapid maxillary expansion (RME) and alternate rapid maxillary expansion and constriction (Alt-RAMEC) followed by facemask (FM) therapy. Methods: The records of 40 patients with skeletal Class lll malocclusion due to maxillary retrognathism were collected, and the patients were assigned into two groups. The first group comprised 8 male and 12 female patients (mean age, 10.0 +/- 1.1 years) treated using RME/FM for an average of 10 months. The second group comprised 10 male and 10 female patients (mean age, 9.64 +/- 1.3 years) treated using Alt-RAMEC/FM for an average of 12 months. Cone-beam computed tomography images acquired before (TO) and after treatment (T1) were evaluated. Results: Regarding the skeletal effects, significant differences between the groups were the increase in ANS-HRP (perpendicular distance of ANS to the horizontal reference plane, 0.99 mm, p <0.05) in the Alt-RAMEC/FM group and the decrease in PP-SN (palatal plane to Sella-Nasion plane, 0.93 degrees, p < 0.05) in the RME/FM group. Maxillary sinus volumes increased significantly in both the groups, and the increase was statistically significantly higher in the AltRAMEC/FM group. Although no significant intergroup differences were observed in PA volumes, both lower (1,011.19 mm(3)) and total (1,601.21 mm(3)), PA volume increased significantly in the Alt-RAMEC/FM group. Conclusions: The different expansion devices and protocols used with FM therapy do not seem to affect the forward movement of the maxilla and PA volumes. In contrast, the increase in maxillary sinus volume was greater in the Alt-RAMEC/FM protocol.
Keywords: Facemask; Airway; Alternate rapid maxillary expansion and constriction; Cone-beam computed tomography; SAGITTAL PHARYNGEAL DIMENSIONS; CLASS-III MALOCCLUSION; AIRWAY DIMENSIONS; SOFT-TISSUE; PROTRACTION; CHILDREN; VOLUME; SIZE